Mechanism of Action of Nalidixic Acid on Escherichia coli IV. Effects on the Stability of Cellular Constituents - Cook, Thomas M. (1966)
Cook, Thomas M. (Sterling-Winthrop Research Institute, Rensselaer, N.Y.), William H. Deitz, and William A. Goss. Mechanism of action of nalidixic acid on Escherichia coli. IV. Effects on the stability of cellular constituents. J. Bacteriol. 91:774–779. 1996.—Treatment of Escherichia coli 15TAU with nalidixic acid resulted in degradation of the nucleic acids of the cells, whereas protein was unaffected. Deoxyribonucleic acid (DNA) degradation appeared to be more extensive than ribonucleic acid degradation during periods of comparable bactericidal action. The onset of DNA degradation was evident prior to a measurable bactericidal effect. However, within the range of 2 to 20%, DNA degradation was accompanied by a decrease in viable cell numbers. Degradation of DNA to acid-soluble material occurred only under conditions permitting the bactericidal action of nalidixic acid. Arrest of the bactericidal action of nalidixic acid by the addition of dinitrophenol or chloramphenicol also inhibited DNA degradation. The acid-soluble products, which were excreted into the medium, have not been characterized completely, but probably were not phosphorylated.